Dendeng Ikan Leubiem (Canthidermis maculatus) dengan Variasi Metode Pembuatan, Jenis Gula, dan Metode Pengeringan - Nida El Husna; Asmawati Asmawati; Gunawan Surwajana (Agricultural Faculty, 2014)
Leubiem fish (Canthidermis maculatus) is one of marine species in Aceh. As a perishable food product, this fish is needed to be processed becoming jerky products to prevent the damage. Jerky is a semi-moist food which is usually made from meat or fish, slab, wide and dried with additional of sugar, salt, spices and others. This study aims to determine the effect of jerk’s making methods (sliced and milled), types of sugars (white sugar and brown sugar), and drying methods (cabinet and sun drying) on the quality of the fish jerky. This study was conducted using a randomized block design (RBD) factorial with three replications. Analysis of the products includes of yields, moisture content, protein content, insoluble acid ash content, and organoleptic test. The results showed that the milled jerky had a higher yield and higher organoleptic texture score than sliced jerky. However, sliced jerky had a lower moisture content and higher protein content than milled jerky. The best quality of leubiem fish jerky was obtained in milled jerky, using white sugar, and sun drying method with the characteristics: yield 51.81%, moisture content 8.20%, protein content 53.94%, insoluble acid ash content 0.36%, and organoleptic tests scores: color 3.28 (neutral), flavor 3.35 (neutral), taste 3.33 (neutral), and texture 3.15 (neutral).